Effects of alliin on renal ischemia reperfusion induced lung injury (Annals of Medical Research, 2021)
Aim: Renal ischemia reperfusion (I/R) injury is a problematic process which leads to renal dysfunction and may be mortal for the patients in intensive care units. Increased oxidant molecules and decreased antioxidant molecules were detected in renal I/R-induced lung injury. In the present study, it was aimed to investigate the effect of Alliin on oxidative stress in renal I/R-induced lung injury. Material and Methods: A total of 32 Wistar Albino male rats were randomly divided into 4 groups (n = 8): Sham, I/R, I/R+Alliin 100 mg/kg and I/R+Alliin 200 mg/kg group. The effects of Alliin on oxidant and antioxidant molecules were evaluated via biochemical methods.Results: Alliin treatment increased antioxidant parameters and decreased oxidant parameters.Conclusion: Alliin has been shown to reduce oxidative stress and renal I/R-induced lung injury.
Keywords: Alliin; kidney ischemia reperfusion; lung; oxidative stress